2009
DOI: 10.1007/s00775-009-0600-y
|View full text |Cite
|
Sign up to set email alerts
|

Copper in the brain and Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common form of neurodegenerative disease. The brain is particularly vulnerable to oxidative damage induced by unregulated redox-active metals such as copper and iron, and the brains of AD patients display evidence of metal dyshomeostasis and increased oxidative stress. The colocalisation of copper and amyloid beta (Abeta) in the glutamatergic synapse during NMDA-receptor-mediated neurotransmission provides a microenvironment favouring the abnormal interaction of redox-poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
224
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 433 publications
(231 citation statements)
references
References 266 publications
0
224
0
7
Order By: Relevance
“…The H6R mutation facilitates zinc‐induced dimerisation of the N terminus;25 however, here we focus exclusively on copper, as it has much stronger interactions with Aβ 26. Furthermore, its interactions with wild‐type Aβ (wt‐Aβ) has been linked with an increase in oligomerisation/fibrillisation, as well as being a source of oxidative damage 27. The coordination environment of copper bound to Aβ has been solved by EPR for both wt‐Aβ and mutants H6R and D7N 28, 29.…”
Section: Introductionmentioning
confidence: 99%
“…The H6R mutation facilitates zinc‐induced dimerisation of the N terminus;25 however, here we focus exclusively on copper, as it has much stronger interactions with Aβ 26. Furthermore, its interactions with wild‐type Aβ (wt‐Aβ) has been linked with an increase in oligomerisation/fibrillisation, as well as being a source of oxidative damage 27. The coordination environment of copper bound to Aβ has been solved by EPR for both wt‐Aβ and mutants H6R and D7N 28, 29.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that deposition of misfolded proteins increases the amount of ROS [37], by causing inflammation in neuroglia, which, in turn, catalyzes ROS formation [38,39]. Aβ, αS, and PrP also complex metal ions, such as FeII and CuI, that strongly catalyze ROS formation [40,41]. Concentrations of CuI and FeII are in amyloid plaques are about twice as high as in surrounding tissues [42].…”
Section: Toxicity and Amyloid Formationmentioning
confidence: 99%
“…6,7 Several in vitro studies have related the formation of the deposits and the observed toxicity to the interaction of Aβ with these metal cations. [8][9][10][11][12][13][14] In this sense, copper has been the most intensively studied [15][16][17][18][19][20][21][22] because of its abundance in the cerebral medium and its high redox activity. In particular, several studies have focused in the determination of the copper coordination center at different pH values by means of continuous wave electron paramagnetic resonance (CW-EPR) and hyperfine sublevel correlation (HYSCORE) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%